Ordinary Aristocrats: The Discursive Construction of Philanthropists as Ethical Leaders - Liu, Helena (Journal of business ethics, 2016)
Philanthropic giving among leaders is often assumed to be an expression of ethical leadership in both academic and media discourses; however, this assumption can overlook the ways in which philanthropy produces and is underpinned by inequality. In order to extend current understandings of ethical leadership, this study employs a critical discourse analytic approach to examine how the link between philanthropy and ethical forms of leadership is verbally and visually constructed in the media. Based on the analysis, the article demonstrates how the construction of Australian philanthropists as ethical leaders is achieved through their representation via three paradoxical identities: Aristocratic Battlers; Caring Controllers; and Publicity-Shy Celebrities. These discourses are mediated by Australian cultural norms and serve to conceal yet ultimately reinforce social and economic inequality. The article proposes that a critical discursive approach to understanding leadership ethics can help to explore the hidden or adverse effects of ostensibly ethical practices.